The power of things and the flow of cultural transformations: art and culture between Europe and Asia - Saurma-Jeltsch, Lieselotte E.; Eisenbeiß, Anja (Dt. Kunstverl., 2010)
"This volume presents contributions from a lecture series held in the winter semester 2009/10 at the University of Heidelberg's Cluster of Excellence 'Asia and Europe in a Global Context: Shifting Asymmetries in Cultural Flows.' The central theme is the power of things--works of art, luxury goods, and ideas--in cultural processes"--P. 8